Protracted case of vaginal prolapse and its remedial measures in a buffalo - SINGH, C P; PRASAD, SHIV; PRASAD, J K; SHAKTAWAT, J S (The Indian Journal of Animal Reproduction, 2023)
Protracted cases of cervico-vaginal/vaginal prolapse can be cured using vaginopexy under good hygienic conditions.However, supportive therapy in the management of the vaginal prolapse is mandatory. Parental administration of calciumpreparation has been found to be beneficial in minimizing the tenesmus. The present technique coupled with parental calciumtherapy could be adequate and effective tool for the management of recurrent/protracted cases of cervico-vaginal/vaginalprolapse in cattle and buffaloes.
Keywords: cervico-vaginal; vaginal prolapse; vaginopexy; calcium therapy